Randomized Comparison of Everolimus- and Zotarolimus-Eluting Coronary Stents With Biolimus-Eluting Stents in All-Comer Patients. (March 2020) - Youn, Young Jin; Lee, Jun-Won; Ahn, Sung Gyun; Lee, Seung-Hwan; Yoon, Junghan; Park, Keum Soo; Lee, Jin Bae; Yoo, Sang-Yong; Lim, Do-Sun; Cho, Jang Hyun; Choi, Cheol Ung; Jeong, Myung Ho; et al.
Abstract : Background: There is limited data comparing the Xience everolimus-eluting stent (EES) and the Resolute zotarolimus-eluting stent (ZES) with the BioMatrix biolimus-eluting stent (BES). Methods: This open-label, randomized, noninferiority trial enrolled all-comer patients to be randomly treated with either BES, EES, or ZES in a 1:1:1 ratio in 15 centers across South Korea. The primary end point was a device-oriented composite outcome consisting of cardiac death, target-vessel myocardial infarction, and clinically indicated target lesion revascularization at 24 months. The BES was compared with the EES and the ZES by intention-to-treat analyses with a noninferiority margin of 3.8%, respectively. Results: Because of slow recruitment and low event rates, this trial was prematurely terminated after enrollment of 1935 (75%) of the intended 2580 patients. Of the 1911 patients randomized to either EES (n=638), BES (n=634), or ZES (n =639), the rate of device-oriented composite outcome was 3.6%, 2.2%, and 3.9%, respectively, at 24 months (BES versus EES: absolute risk difference −1.4% [upper limit of 1-sided 95% CI: −3.2%]; P for noninferiority <0.001; BES versus ZES: absolute risk difference −1.7% [upper limit of 1-sided 95% CI: −3.6%]; P for noninferiority <0.001). Conclusions: The BES was noninferior to either the EES or the ZES in all-comer patients for device-oriented composite outcome at the 24-month follow-up. However, caution is advised regarding interpretation of these results due to the premature termination of this study. Registration: URL: https://www.clinicaltrials.gov ; Unique identifier: NCT01397175.